Melt electrowriting of poly(vinylidene fluoride‐co‐trifluoroethylene). Issue 12 (14th July 2021) - Kade, Juliane C; Tandon, Biranche; Weichhold, Jan; Pisignano, Dario; Persano, Luana; Luxenhofer, Robert; Dalton, Paul D
Abstract: Poly(vinylidene fluoride‐ co ‐trifluoroethylene) (P(VDF‐co‐TrFE)) is an electroactive polymer with growing interest for applications in biomedical materials and flexible electronics. In this study, a solvent‐free additive manufacturing technique called melt electrowriting (MEW) has been utilized to fabricate well‐defined microperiodic structures of the copolymer (P(VDF‐co‐TrFE)). MEW of the highly viscous polymer melt was initiated using a heated collector at temperatures above 120 °C and required remarkably slow collector speeds below 100 mm min −1 . The fiber surface morphology was affected by the collector speed and an increase in β‐phase was observed for scaffolds compared to the unprocessed powder. Videography shows vibrations of the P(VDF‐co‐TrFE) jet previously unseen during MEW, probably due to repeated charge buildup and discharge. Furthermore, piezo‐force microscopy measurements demonstrated the electromechanical response of MEW‐fabricated fibers. This research therefore achieves the melt electrohydrodynamic processing of fibers with micrometer resolution into defined structures with an important electroactive polymer. © 2021 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry. Abstract : Melt electrowriting (MEW) is a solvent‐free 3D printingtechnology that enables fiber processing with low micron range diameters. Inthis study, the electroactive copolymer poly(vinylidene fluoride‐co‐trifluoroethylene)is successfully processed into defined fibers using MEW, enabled via a heated collector.The printed material has higher β‐phasecontent compared to unprocessed powder, and individual fibers change shape uponcooling.